PENGAWETAN LIMA JENIS KAYU DENGAN KOPPERS FORMULA 7 MENURUT METODE PENCELUPAN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Five timber species were treated with Koppers Formula 7 using momentary immersion method. The samples (5 cm x 5 cm x 100 cm) were then introduced into a diffusion chamber for one, three, or jive weeks. The depth of penetration was measured after cutting the samples and result analyzed. The conclusions are :The duration of diffusion has a highly significant effect on preservative penetration, while the timber species did not have a significant bearing in the penetration. The rate of diffusion is proporsional to the treatment time.Taking the forgoing result into account, the moisture content has no effect on the depth of penetration.The momentary immersion method appeared to have met to the standar requirement for all timber species tested in this experiment.The result indicated that duration in one week gives statisfactory penetration for the mahoni, manii and jeungjing species. The durian and petai however, could only give statisfactory results when the duration is longer than three weeks